Evaluation of antioxidant and antimicrobial properties of solvent extracts of agro-food by-products (cashew nut shell, coconut shell and groundnut hull) - Prakash, Anand; Vadivel, Vellingiri; Banu, Sanaulla Farisa; Nithyanand, Paramasivam; Lalitha, Cheepurupalli; Brindha, Pemaiah (Agriculture and Natural Resources, 2018)
In India, agro-food by-products such as shell cake of cashew nut (Anacardium occidentale L.), shell of coconut (Cocos nucifera L.) and hull of groundnut (Arachis hypogaea L.) are cheaply available on a vast scale. Even though a small portion of these solid waste materials is being used, a large quantity is not being utilized. Based on literature data, these by-products could be used as a source of valuable phytochemicals. The present study explored a suitable solvent system and extraction conditions for the recovery of polyphenols from three different agro-food by-products. The optimal conditions for the recovery of polyphenols from agro-food by-products were investigated in addition to evaluating their antioxidant and antibacterial properties. Among the three investigated by-products, methanolic extract of cashew nut shell was the most prominent source of antioxidants (3412.28 mg gallic acid equivalent (GAE)/L) compared to coconut shell (1056.32 mg GAE/L) and groundnut hull (426.35 mg GAE/L). The in vitro antioxidant assay produced promising radical scavenging activity of shell extract of coconut (concentration at which the response was reduced by half; IC50=12 mg/mL) compared to cashew nut (IC50 =44 mg/mL) and groundnut hull extract (IC50=48 mg/mL). The anti-bacterial activity of different solvent extracts revealed that the methanolic extracts from cashew nut and coconut shells were more effective in inhibiting the growth of both Gram-positive and Gram-negative bacteria. The present work revealed the possibility of recovery of useful phytochemical compounds from agro-food byproducts which could be used subsequently as natural food preservatives.